Antiviral use in liver function abnormalities and Covid-19 patients: Serial cases - Intan Rizkia Dewi (Elsevier, 2022)
Introduction: Some SARS-CoV-2 patients have liver function abnormalities due to anti-viral drug effects. Methods: The design of this study was a case series reported using retrospectives. Data collection was carried out from December 2020 to February 2021. All participants were diagnosed with SAR-CoV-2 and received an antiviral drug which identified liver function abnormalities. Results: The patients’ average age was 54.56 ± 14.46 years old. Most patients experienced shortness of breath and cough, with hypertension as the accompanying comorbid. Increased AST and ALT were found in one patient who used Lopinavir-Ritonavir. The increase was 1.0 times to 2.0 times the expected value. Increased CRP, Ddimer and procalcitonin were also found, with a mean of 12.27 ± 15,34, 1861.29 ± 1828.85 and 1.54 ± 2.84, respectively. One of the patients in the Lopinavir-Ritonavir group died while receiving treatment. Conclusion: SAR-CoV-2 is one of the risk factors that cause liver function abnormalities supported by anti-viral drugs that cause liver work to increase.